Memikirkan Kembali Pendidikan Tinggi bagi Pemuda Pedesaan: Menjembatani Penghidupan Pertanian dan Aspirasi Pendidikan melalui Studi Lapangan - Kasmanita Kasmanita; Hilmiah Hilmiah; Muh. Fitratallah Dahlan; Munira Hamzah; Mustabsyirah Mustabsyirah (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
Education is an important part of improving the quality of human resources, including for rural communities. This study aims to find out the reason for the low interest of the young generation in Batuampa Village to continue their education to higher education and prefer to work in the plantation sector. Using a qualitative descriptive method, research data was obtained through interviews and direct observation. The results of the study showed that low interest in studying was influenced by the comfort of working in the garden, own land ownership, low academic confidence, flexibility of working hours, and lack of university socialization and scholarship information. In addition, higher education is still considered less relevant to the practical needs of society. This study confirms that the integration of higher education with the plantation sector has the potential to increase the interest of the younger generation if education is understood as a means to improve knowledge, skills, and sustainability of plantation businesses.